2019
DOI: 10.1186/s12912-019-0382-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study exploring the relationship between burnout, absenteeism, and job performance among American nurses

Abstract: BackgroundStudies suggest a high prevalence of burnout among nurses. The aim of this study was to evaluate the relationship between burnout among nurses and absenteeism and work performance.MethodsA national sample of U.S. nurses was sent an anonymous, cross-sectional survey in 2016. The survey included items about demographics, fatigue, and validated instruments to measure burnout, absenteeism, and poor work performance in the last month.ResultsOf the 3098 nurses who received the survey, 812 (26.2%) responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
3
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 57 publications
7
165
3
15
Order By: Relevance
“…Regarding burnout dimensions, higher levels of burnout sub scores have been reported in a meta-analysis by Gómez-Urquiza et al [33]. As compared to our study, Dyrbye et al [34] reported higher mean scores in all three subscales in the USA. Apart from differences in working departments, schedules patients' workloads and management policies that are apparent between countries, non-response, and social desirability biases could also play a role in explaining the differences as these are cross-sectional studies.…”
Section: Plos Onesupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding burnout dimensions, higher levels of burnout sub scores have been reported in a meta-analysis by Gómez-Urquiza et al [33]. As compared to our study, Dyrbye et al [34] reported higher mean scores in all three subscales in the USA. Apart from differences in working departments, schedules patients' workloads and management policies that are apparent between countries, non-response, and social desirability biases could also play a role in explaining the differences as these are cross-sectional studies.…”
Section: Plos Onesupporting
confidence: 56%
“…On the other hand, our study had four (4) dependent variables, namely; emotional exhaustion, depersonalization, and personal achievement (i.e., defining burnout) and favorability to the work environment. For the descriptive purpose, emotional exhaustion was grouped as low (if scores <19), moderate (if scores [19][20][21][22][23][24][25][26] or high (if scores >26); depersonalization grouped as low (if scores <6), moderate (if scores 6-9) and personal achievement grouped as low (<34), moderate (34)(35)(36)(37)(38)(39) and high (>39); and lastly favorability to the work environment condition was classified as favorable (if 4 or 5 sub-scores were > 2.5); mixed (if 3 or 2 sub-scores were >2.5) and unfavorable (if none sub-scores were >2.5). For analytical purposes, WES was treated as a categorical variable while other aforementioned variables as continuous.…”
Section: Variablesmentioning
confidence: 99%
“…An increase in the overall burnout rate of the MBI questionnaire by 1 point increases the probability that an employee will take at least three sick leaves per year by 2.9%. Similar correlation between burnout and absenteeism was found in the United States (Dyrbye et al, 2019) and Brazil (Da Silva and Diaz Merino, 2017), but no regression model presenting detailed correlation parameters was developed. A Danish team of researchers, however, identified occupational burnout as a predictor of sickness absence among human service workers (Borritz et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Currently, only a limited number of studies have explored the factors associated with the well‐being of nurses in China, but studies can be found in the literature that explored burnout and job satisfaction. A national survey in the USA suggested that burnout is prevalent among nurses and likely leads to absenteeism and impacts work performance (Dyrbye et al, ). Low levels of job satisfaction are a key factor associated with turnover and retention rates among nurses (Bai et al, ; Hairr, Salisbury, Johannsson, & Redfern‐Vance, ), as well as their intentions to leave the workplace (Ramoo, Abdullah, & Piaw, ; Sveinsdottir & Blondal, ).…”
Section: Introductionmentioning
confidence: 99%